THE RELATIONSHIP BETWEEN AGE, PARITY, AND BIRTH WEIGHT WITH THE DEGREE OF PERINEAL RUPTURE IN THE RSUD JAYAPURA - Yuni Hukubun; Dwi Izzati Budiono; Eighty Mardiyan Kurniawati (UNIVERSITAS AIRLANGGA, 2021)
AbstractBackground: Perineal rupture is a condition in which the perineum is torn as a result of vaginal delivery either by action or not, which affects the health status of women. Age, parity, and birth weight are influencing factors for perineal rupture.The aim of this study was to analyze the relationship between age, parity, and birth weight with the degree of perineal rupture. Methods: Observational analytic research with a case control approach. The sample used in this study were the patients who get diagnostic of perineal rupture during April – December 2019 in the RSUD Jayapura as many as 654 patients. The sampling technique used is total sampling. The independent variables used were age, parity, and birth weight, while the dependent variable was perineal rupture. Bivariate analysis test using Spearman rank correlation. Multivariate analysis test using multiple logistic regression with backward method. Results: The results of the bivariate analysis in this study was showing that the younger mother's age, lower paratity values and higher birth weight related with the degree of perineal rupture, then the multivariate results obtained birth weight had a dominant effect of degree perineal rupture. This is because the heavy of birth weight make the perineum more strecthcing, so the perineum gets more thinner and easier to rupture. Conclusion: There is a relationship between age, parity, and birth weight with the degree of perineal rupture. Birth weight is the most dominant independent factor on the degree of perineal rupture. So, it is necessary to give education about childbirth preparation and preconception counseling to mothers.